The Development of Electronic Football Teaching Materials (E-Book) - Amir Supriadi; Mesnan Mesnan; Filli Azandi; Indra Kasih (Budapest International Research and Critics University, 2021)
This study aims to produce electronic soccer teaching materials (ebooks) in basic soccer subjects. This study uses research and development methods by developing electronic soccer teaching materials based on competency standards through needs analysis from lecturers and students. Based on the results of the needs analysis for soccer course lecturers, 90% and 95% of students taking basic soccer courses stated that it was necessary to develop electronic soccer teaching materials for the needs of basic soccer lectures. The results of the validation of the feasibility of content, media feasibility and material feasibility obtained an average of 77.7% (very good) for content feasibility: 81.7% (very good) for media feasibility: and 80.3 (very good) good) for the feasibility of the material. With the average validation result of the three components is 79.9% (very good). The results of the effectiveness test of electronic soccer teaching materials in small-scale trials obtained an average percentage of 89.6%. In testing the effectiveness of electronic soccer teaching materials in small-scale trials, an average percentage of 91.4% was obtained.The conclusion is that the electronic soccer teaching materials developed can be used in online and offline basic soccer lectures.